Adopt strategies for listening actively. Issue 12 (April 2017) - Zachary, Lois J.; Fischler, Lory A.
Abstract : The material on this page is excerpted from Starting Strong: A Mentoring Fable. The authors explain strategies for active listening in a mentoring situation. Their advice could also apply to many other situations where listening is critical .